A Retrospective Pragmatic Longitudinal Case-Series Clinical Study to Evaluate the Clinical Outcome of Triple-Frequency Ultrasound in Treatment of Cellulite - Chervinskaya I; Kuprina NI; Kruglikov I (Clinical, Cosmetic and Investigational Dermatology)
Irina Chervinskaya,1 Nadezhda I Kuprina,2 Ilja Kruglikov3 1Clinic DK Forma, St. Petersburg, Russian Federation; 2North-West Public Health Research Center, St. Petersburg, Russian Federation; 3Wellcomet GmbH, Bruchsal, GermanyCorrespondence: Ilja Kruglikov, Email i.kruglikov@wellcomet.deObjective: In this single-centre, retrospective, pragmatic, longitudinal case-series clinical study triple-frequency LDM (TF-LDM) technology with frequencies of 1/3/10 MHz and 3/10/19 MHz was applied for treatment of cellulite to reveal the effect of these waves on the cellulite skin and assess the sustainability of treatment outcomes during the long-term follow-up controls.Methods: Twenty Caucasian females with mild-to-severe gynoid lipodystrophy aged 27– 53 years who received cellulite monotherapy with TF-LDM were included in this study. All participants were evaluated at three time points: baseline (T1), on the day of the last treatment (T2), and during the last follow-up (T3). Cellulite severity was assessed by six independent clinicians using the five-grade Clinician-Reported Photonumeric Cellulite Severity Scale (CR-PCSS). Patient satisfaction was evaluated using a 10-grade GAIS scale, ranging from 0 to 10 (0 - dissatisfied; 10 - fully satisfied). To objectify the treatment outcomes, 17 subjects were investigated using B-mode ultrasonography and real-time compression elastography at baseline and during follow-up.Results: The average values of CR-PCSS (T1), CR-PCSS (T2) and CR-PCSS (T3) over all participants were 2.22± 0.82, 1.18± 0.77, and 0.84± 0.77, respectively, which corresponded to the skin improvement between T1 and T2 of 0.93± 0.27 (p < 0.0001) as well as between T1 and T3 of 1.38± 0.47 (p < 0.0001). Assessment of elasticity of the dermis and adipose tissue on the basis of the 5-grade coloration scale revealed significant reinforcement of both tissues as well as of the superficial fascia at follow-up as compared to their baseline values. The obtained treatment outcomes were long-lasting and could be clearly observed even in individuals with a long-term follow-ups. Assessment of the satisfaction of participants with the treatment results revealed a high satisfaction of 8.95 ± 1.49. The method demonstrated no side effects, was pain-free, well-tolerated, and highly accepted by patients.Keywords: single-centre, retrospective clinical study, cellulite, triple-frequency ultrasound